A STUDY ON THE MENTAL HEALTH OF UENF POSTGRADUATE STUDENTS - Anzolin Lichote, Davis; Moss Simões dos Reis, Verusca (LINKSCIENCEPLACE, 2026)
This research aimed to investigate the main stressors among stricto sensu graduate students enrolled in master’s and doctoral programs at the State University of Northern Fluminense (UENF). Questionnaires regarding the Perceived Stress Scale and an inventory on the problems and difficulties faced by graduate students at the university were administered. A total of 161 students from all UENF graduate programs participated in the study. The sample predominantly consisted of females, accounting for 67.3% of the total participants, aged between 22 and 58 years, with an equitable percentage distribution between master’s and doctoral students. As a result, 71.2% of respondents reported feeling stressed to some extent. The students identified "internal pressure for good academic performance" as the most significant factor of concern, and 81.4% of respondents stated that "the need for publication"was the greatest difficulty faced in their graduate studies.